Korelasi Pola Asuh dan Motivasi Belajar dengan Prestasi Matematika Siswa SMA Kusuma Bangsa Palembang - Andri Wijaya; Mujiyanto Mujiyanto; Alexander Chandra (Institut Nalanda, 2025)
The Correlation between Parenting Patterns and Learning Motivation to Student Learning Outcomes in Mathematics Subjects at SMA Kusuma Bangsa Palembang. Buddhist Religious Education Thesis, Nalanda Institute, Dr. Mujiyanto, S.Pd., M.Pd. as first advisor and Dr. Alexander Chandra, M.M., M.Kn., MBA as second advisor. This research was aimed to determine the correlation between parenting patterns and learning motivation to student learning outcomes in mathematics subjects at SMA Kusuma Bangsa Palembang. The hypothesis proposed in this study is that there is a correlation between parenting patterns and learning motivation to student learning outcomes in mathematics subjects at SMA Kusuma Bangsa Palembang. The sample in this research amounted to 135 students of class X. The measuring instrument in data collection used a scale of parenting patterns, a scale of learning motivation, and a scale of student learning outcomes in mathematics, with a correlational method as a research method. The results showed that the correlation coefficient of 0.726 indicated a positive relationship and high interpretation. The Fcount value = 7.071, Ftable (0.05; 135) = 3.060 with the criteria Fcount > Ftable, so that the null hypothesis (Ho) which states that there is no correlation between parenting patterns and learning motivation on student learning outcomes in mathematics subjects at SMA Kusuma Bangsa Palembang is rejected. Thus, there is a significant positive correlation between parenting patterns and learning motivation on student learning outcomes in mathematics at SMA Kusuma Bangsa Palembang with multiple regression analysis y = 73.178 + 0.164X1 + 0.183X2 which is real. The magnitude of the effective contribution of parenting patterns and learning motivation to student learning outcomes in mathematics at SMA Kusuma Bangsa Palembang is 52.7%, while the remaining 47.3% is caused by other factors.